2022
DOI: 10.1038/s41598-022-15490-2
|View full text |Cite
|
Sign up to set email alerts
|

Monovalent ions and stress-induced senescence in human mesenchymal endometrial stem/stromal cells

Abstract: Monovalent ions are involved in growth, proliferation, differentiation of cells as well as in their death. This work concerns the ion homeostasis during senescence induction in human mesenchymal endometrium stem/stromal cells (hMESCs): hMESCs subjected to oxidative stress (sublethal pulse of H2O2) enter the premature senescence accompanied by persistent DNA damage, irreversible cell cycle arrest, increased expression of the cell cycle inhibitors (p53, p21) cell hypertrophy, enhanced β-galactosidase activity. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 93 publications
0
0
0
Order By: Relevance
“…Later, during senescence progression, the Na + content is slightly increased and the pumpmediated K + transport is enhanced. The higher K + influxes in "late" stressed senescent eMSCs are not associated with modulation of the Na/K pump properties or an increased number of ion pumps but are due to higher cell Na + content in late senescence [25]. Stressinduced proliferation arrest does not affect the ouabain-resistant K + fluxes associated with the activity of ion channels and ion co-transporters.…”
Section: K + and Proliferation Arrest: Lower Cell K + Content Accompa...mentioning
confidence: 86%
See 3 more Smart Citations
“…Later, during senescence progression, the Na + content is slightly increased and the pumpmediated K + transport is enhanced. The higher K + influxes in "late" stressed senescent eMSCs are not associated with modulation of the Na/K pump properties or an increased number of ion pumps but are due to higher cell Na + content in late senescence [25]. Stressinduced proliferation arrest does not affect the ouabain-resistant K + fluxes associated with the activity of ion channels and ion co-transporters.…”
Section: K + and Proliferation Arrest: Lower Cell K + Content Accompa...mentioning
confidence: 86%
“…Fluorescent probes have revealed an increased content of both K + and Na + in the senescent human lung fibroblast IMR90 [40]. However, thorough estimations of ions in cells with the flame photometry technique have shown that stressinduced senescent human eMSCs have low Na + and maintain a high K + /Na + ratio typical for functionally active animal cells [25]. Indeed, short oxidative stress leads to a decrease in intracellular K + content and an increase in Na + content in eMSCs; however, within a day, in "early" stress-arrested cells, the ionic gradients and ion pump activity are restored (Figure 2).…”
Section: K + and Proliferation Arrest: Lower Cell K + Content Accompa...mentioning
confidence: 99%
See 2 more Smart Citations
“…Short treatment with 200 μM H 2 O 2 of subconfluent eMSCs cultures has been shown to induce senescence [31]. eMSCs subjected to sublethal oxidative stress enter into irreversible cell cycle arrest and exhibit a senescent phenotype including p53/p21/Rb mediated cell cycle arrest, cell hypertrophy, enhanced β-galactosidase staining [31,32].…”
Section: K + Transport During Senescence Progression Of Human Mesench...mentioning
confidence: 99%